Comprehensive Therapy for Infant Vascular Tumor Associated With Kasabach–Merritt Phenomenon—Single-Center Primary Experience - Sun, Xiaoting; Xu, Miao; Lv, Kaiyang; Ma, Xiaorong; Wu, Liming; Ouyang, Tianxiang (Frontiers in Pediatrics, 2022)
Objective: To introduce our single-center experience of infant vascular tumor associated with Kasabach-Merritt phenomenon (KMP) which received combined medicine treatment with intralesional laser photocoagulation (ILP) and sclerotherapy. Methods: A retrospective study was conducted of medical records of all children with diagnosis of kaposiform hemangioendothelioma( KHE) or tufted angioma (TA) associated with KMP treated with medicine treatment, intralesional laser photocoagulation (ILP) and sclerotherapy between February 2017 to November 2020. Clinical features, response to comprehensive therapy and outcomes were recorded. Results:Twenty-three patients, including nine females (39%) and fourteen males (61%), were identified. The mean age was 6.9 months (age range, 11 days to 2 years) at the time of treatment. Nine children (39%) demonstrated sensitivity to single corticosteroid therapy. Fourteen children (61%) received combining therapy with intravenous VCR and corticosteroid therapy. All children had at least two ILP and sclerotherapy performed, with a mean of 3.5 procedures (range: 2-6). Of these 14 children, only one experienced a relapse of thrombocytopenia and the remaining 13 children had no clinical symptoms recurred but non-involuting tumor. Conclusions: The combined therapy modalities could induce a more rapid tumor response and resolution of KMP, decrease the rebound rates. The precent research presents a noval and safe multi-modality treatment for infant vascular tumor associated with KMP.